The Lender of Last Resort - Capie, Forrest H; Wood, Geoffrey E. (Oxon: Routledge, 2007)
The capacity of national central banks to step in and bail out an economy is one which has proved to be very important over the years. This collection from Wood and Capie brings together the most import- ant literature for the first time in book form.
Includes Index.
rpm 05/09/13
Loan
Keywords: Bank liquidity; Lenders of last resort; Banks and banking, central